2019
DOI: 10.1016/j.intfin.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory adoption of IFRS in Latin America: A boon or a bias

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
4
0
5
Order By: Relevance
“…In summary, the analysis evidenced that enforcement in the context of IFRS and its impact on accounting quality is a topic that is still in the early stages of research, and must be looked into further. This corroborates the opinion of researchers who argue that few studies actually assess the enforcement practices of countries (Böcking et al, 2015;Guerreiro et al, 2020;Kleinman et al, 2019;Mantzari and Georgiou, 2019;de Moura and Gupta, 2019;Preiato et al, 2015;Silva and Rodrigues, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In summary, the analysis evidenced that enforcement in the context of IFRS and its impact on accounting quality is a topic that is still in the early stages of research, and must be looked into further. This corroborates the opinion of researchers who argue that few studies actually assess the enforcement practices of countries (Böcking et al, 2015;Guerreiro et al, 2020;Kleinman et al, 2019;Mantzari and Georgiou, 2019;de Moura and Gupta, 2019;Preiato et al, 2015;Silva and Rodrigues, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The second most discussed topic is "enforcement." However, out of the 46 papers selected for the period under analysis, only 11% (5) focus on the study of IFRS enforcement, which corroborates the opinion of several authors who claim that studies on enforcement mechanisms of the various countries are scarce (Böcking et al, 2015;Guerreiro et al, 2020;Mantzari and Georgiou, 2019;de Moura and Gupta, 2019;Preiato et al, 2015).…”
Section: Main Findings: Description and Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…There are several future lines of research, for instance, recently, De Moura and Gupta (2019) found a positive effect between IFRS adoption in analysts’ information environment, but it remains to analyze whether there is also an improvement in the analysts’ consensus forecast. Furthermore, De Moura et al (2020) also found that IFRS adoption reduced the firm’s cost of equity and its cost of debt, but we may wonder whether the country risk will be also affected by this IFRS adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is mandatory, low enforcement (Brown et al ., 2014; De Moura and Gupta, 2019) and the absence of sanctions to implement the standard may imply firms are not complying with the standard. Anecdotal evidence suggests that firms have been slow to implement the standard (Meirelles, 2012).…”
Section: Introductionmentioning
confidence: 99%